Investigating the effect of social networks on changing personality traits of students of Islamic Azad University, West Tehran Branch - Saeed tavakkoli; Mohammad hadi Mansour lakoorej (Institute of Management fekrenoandish, 2020)
The present study examines the effect of social networks on changing personality traits of students of Islamic Azad University, West Tehran Branch. The statistical population of this study included master's degree students of Azad University, West Tehran Branch. According to Morgan's table, 260 people were selected using a simple random sampling method. Data collection tools and information in this study included a social media researcher-made questionnaire and Goldberg's (1999) Personality Characteristics Questionnaire. The findings of this study showed that 47% of the explanations for variance related to changing personality traits of students of Islamic Azad University, West Tehran Branch are affected by social networks. Also, the results of regression analysis analysis of constant value and coefficient of variables of usage rate, type of use and level of trust in users were 0.222, 0.295, 0.174 and 0.423, respectively, and according to the statistical value of t-test and A significant level of less than 0.05 was confirmed by the presence of constant coefficients of regression coefficients and coefficients of variables of usage, type of use and level of trust in users. The results of this study showed that social networks have an effect on changing the personality traits of students of Islamic Azad University, West Tehran Branch.